2010
DOI: 10.1111/j.1740-8261.2010.01754.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Operator Exposure for Hand Holding Portable X‐ray Units During Imaging of the Equine Distal Extremity

Abstract: Hand holding of portable X-ray units is common in large animal ambulatory veterinary practice. Portable X-ray equipment manuals, veterinary teaching institutions, and state regulations discourage, or prohibit, hand holding of portable X-ray units. Our goal was to quantify surface radiation leakage of a typical portable X-ray unit and to measure operator exposure at simulated hand and collar positions during imaging of the equine distal extremity. Each exposure for the study was performed at 80 kVp and 7.5 mAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…Similar to our results, it was concluded that personnel dose was extremely low, in the range of 2–49 microsievert. In this range, personnel exposure would not be expected to exceed the annual occupational dose for adults of 0.5 sievert set forth by the institution's state Radiation Protection Commission, especially when compared to a recent study of operator exposure during hand holding of portable x‐ray units for equine imaging . In conclusion, by incorporating the principles of ALARA into technique optimization using an objective endpoint, a single technique is not appropriate for all imaging studies of small animal patients.…”
Section: Discussionmentioning
confidence: 96%
“…Similar to our results, it was concluded that personnel dose was extremely low, in the range of 2–49 microsievert. In this range, personnel exposure would not be expected to exceed the annual occupational dose for adults of 0.5 sievert set forth by the institution's state Radiation Protection Commission, especially when compared to a recent study of operator exposure during hand holding of portable x‐ray units for equine imaging . In conclusion, by incorporating the principles of ALARA into technique optimization using an objective endpoint, a single technique is not appropriate for all imaging studies of small animal patients.…”
Section: Discussionmentioning
confidence: 96%
“…The veterinarians were mainly managing the generator, while the horse owners or other handlers mainly were holding the image detector plate, which is in agreement with what was found in other European countries . Previous studies have shown that the person that is closest to the primary beam and the origin of the scattered radiation receives the highest radiation exposures . This position is most often filled by non‐members of staff who lack knowledge of radiation protection.…”
Section: Discussionmentioning
confidence: 99%
“…Hand holding of generators not only increases the risk of motion blur, but also should be avoided because of the resulting radiation exposure to the person holding it (Tyson et al . ). Patient motion is especially common in poorly sedated, neurologically abnormal or fractious horses, and ensuring that the patient is appropriately restrained is vital to obtaining high‐quality images.…”
Section: Artefacts and Pitfallsmentioning
confidence: 97%
“…Motion of the x-ray generator can be secondary to a pendulum effect when the generator is suspended from the ceiling or a stand; it is important to stabilise the generator to stop this motion prior to image acquisition. Hand holding of generators not only increases the risk of motion blur, but also should be avoided because of the resulting radiation exposure to the person holding it (Tyson et al 2011). Patient motion is especially common in poorly sedated, neurologically abnormal or fractious horses, and ensuring that the patient is appropriately restrained is vital to obtaining high-quality images.…”
Section: Artefacts and Pitfallsmentioning
confidence: 99%